Influence of EGF and pro-NGF on EGFR/SORTILIN interaction and clinical impact in head and neck squamous cell carcinoma - Morisse, Martin; Bourhis, Thomas; Lévêque, Romain; Guilbert, Mathieu; Cicero, Julien; Palma, Martine; Chevalier, Dominique; le Bourhis, Xuefen; Toillon, Robert-Alain; Mouawad, Francois (Frontiers in Oncology, 2023)
Head and Neck Squamous Cell Carcinoma (HNSCC) remains a cancer with a poor prognosis with less than 50% 5-year survival. Although the Epidermal Growth Factor Receptor (EGFR) is strongly over-expressed, targeted anti-EGFR therapies are modest in effectiveness and are mainly used in palliative care. It has already been shown in our laboratory that growth factors like the Nerve Growth Factor (NGF) and its precursor pro-NGF play a role in tumor growth and aggressiveness. Interestingly, an interaction between Sortilin, a pro-NGF receptor and EGFR has been observed. This interaction appears to interfere with the pro-oncogenic signaling of EGF and modulate the membrane expression of EGFR. The objectives of this study are to characterize this interaction from a biological point of view, to assess its impact on the clinical prognosis and to analyze its role in the cellular traffic of EGFR. By immunohistochemical labeling, on tumor sections of patients treated in our university center, and PLA (Proximity Ligation Assay) labeling, we demonstrate that the expression of Sortilin is significantly associated with a reduction of survival at 5 years. But when Sortilin is associated with EGFR, this correlation is not found. Using Cal-27 and Cal-33 cancer cell lines, we observed that pro-NGF decreases the effects of EGF on cell growth by inducing the internalization of its receptor. These results therefore suggest a regulatory role for Sortilin in the degradation or renewal of EGFR on the membrane. It would be interesting in future work to show the intracellular fate of EGFR and the role of (pro) neurotrophins in these mechanisms.